Serum MicroRNA-21 as Marker for Necroinflammation in Hepatitis C Patients with and without Hepatocellular Carcinoma - Bihrer, Verena (Public Library of Science, 2011)
BACKGROUND: MicroRNA-21 (miR-21) is up-regulated in tumor tissue of patients with malignant diseases, including hepatocellular carcinoma (HCC). Elevated concentrations of miR-21 have also been found in sera or plasma from patients with malignancies, rendering it an interesting candidate as serum/plasma marker for malignancies. Here we correlated serum miR-21 levels with clinical parameters in patients with different stages of chronic hepatitis C virus infection (CHC) and CHC-associated HCC. METHODOLOGY/PRINCIPAL FINDINGS: 62 CHC patients, 29 patients with CHC and HCC and 19 healthy controls were prospectively enrolled. RNA was extracted from the sera and miR-21 as well as miR-16 levels were analyzed by quantitative real-time PCR; miR-21 levels (normalized by miR-16) were correlated with standard liver parameters, histological grading and staging of CHC. The data show that serum levels of miR-21 were elevated in patients with CHC compared to healthy controls (P<0.001); there was no difference between serum miR-21 in patients with CHC and CHC-associated HCC. Serum miR-21 levels correlated with histological activity index (HAI) in the liver (r = −0.494, P = 0.00002), alanine aminotransferase (ALT) (r = −0.309, P = 0.007), aspartate aminotransferase (r = −0.495, P = 0.000007), bilirubin (r = −0.362, P = 0.002), international normalized ratio (r = −0.338, P = 0.034) and γ-glutamyltransferase (r = −0.244, P = 0.034). Multivariate analysis revealed that ALT and miR-21 serum levels were independently associated with HAI. At a cut-off dC(T) of 1.96, miR-21 discriminated between minimal and mild-severe necroinflammation (AUC = 0.758) with a sensitivity of 53.3% and a specificity of 95.2%. CONCLUSIONS/SIGNIFICANCE: The serum miR-21 level is a marker for necroinflammatory activity, but does not differ between patients with HCV and HCV-induced HCC.